JIHAD DALAM HUKUM ISLAM: REINTERPRETASI DARI QITĀL MENUJU ETIKA PERJUANGAN - Siti Khofifah; Abd Rahman R; Rahmatiah HL (PT. Saha Kreasi Indonesia, 2025)
This study aims to reinterpret the concept of jihad within Islamic law in order to clarify its comprehensive meaning and address widespread misconceptions that equate jihad solely with physical violence or warfare. The research employs a qualitative library research design using a normative-theological approach. Primary data are derived from the Qur’an and Hadith, while secondary data consist of classical and contemporary Islamic legal texts, scholarly books, and peer-reviewed journal articles relevant to the discourse on jihad. Data were collected through systematic documentation and analyzed using descriptive-analytical methods to examine the textual foundations, classifications, and objectives of jihad in Islamic jurisprudence. The findings reveal that jihad in Islamic law encompasses multidimensional forms of struggle, including spiritual self-discipline, intellectual and moral efforts, da‘wah, patience, and social responsibility, while armed struggle (qitāl) is limited to specific defensive contexts under strict ethical and legal regulations. This study argues that reducing jihad to warfare reflects a contextual and interpretative distortion rather than the normative teachings of Islam. The novelty of this research lies in its emphasis on jihad as an ethical framework of struggle rooted in justice, humanity, and the preservation of social harmony, rather than as a symbol of violence. The implications of this study are significant for Islamic education, as it provides a balanced and contextual understanding of jihad that can be integrated into curricula to counter radical interpretations and promote peaceful coexistence. This research is expected to serve as a reference for future studies on Islamic legal concepts and their contemporary applications.